A YOUNG FEMALE PATIENT WITH NEUROFIBROMATOSIS TYPE II: RARE CONDITION HAVING SHORT HISTORY WITH HUGE PARASAGITTAL MENINGIOMA - Saeed Mazher (Journal of University Medical & Dental College, 2013)
ABSTRAT Neurofibromatosis is a rare neoplastic disease with which we come across. In addition to that a very large Parasagittal Meningioma was encountered which has invaded across the anterior & middle superior sagittal sinus. It may present with spinal tumors. The case of Neurofibromatosis type II we present in a young female patient who had a history of loss of vision, head ache, decrease hearing from left side and single episode of fits for the last few months. She was managed initially conservatively then surgical intervention was contemplated in two stages. In first stage the hyperostotic bone flap was removed and placed in abdomen. Then while removing tumor in the next stage the anterior one third of the superior sinus was tied and separated from the falx for attempting the complete removal.